Istikhdām al-Maʿajim al-Lughawiyyah fī Taʿalum al-Lughah al-ʿArabiyyah Lada Ṭalabah Jāmiʿah Janūb Sharq Unmūdhajan - A.R.F.S. Farween; M.S. Zunoomy (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Dictionaries play major role in providing meanings and information of vocabulary in a language. language learners take benefits widely from these dictionaries in developing their language proficiency. This study focuses the extent of the use of language dictionaries and their types among students in the Department of Arabic Language at South Eastern University of Sri Lanka who learn Arabic as a foreign language and use it as the language tool for their subjects in their university studies. This study uses the descriptive method to analyze the primary data gathered from the questionnaire and the secondary data also, while the questionnaire is distributed in Tamil language among the students of first year. The study finds that the most of the students learn Arabic alongside their mother tongue, and they also use electronic dictionaries and Google translation to understand the meanings of obscure words in their learning of the Arabic language, and they prefer bilingual and trilingual dictionaries than monolingual dictionaries, and they indicate that the use of machine translation and lack of knowledge of using dictionaries and unwillingness to use them are reasons for the lack of use of language dictionaries among them.إن المعاجم تأخذ دورا فعالا في تقديم مفاهيم المفردات ومعلوماتها في لغة ما. أما متعلمو اللغة فهم يستفيدون بهذه المعاجم استفادة كبيرة في تنمية حصيلتهم اللغوية. فهذه الدراسة تبحث عن مدى استخدام المعاجم اللغوية وأنواعها لدى طلبة في قسم اللغة العربية في جامعة جنوب شرق سريلانكا الذين يتعلمون اللغة العربية لغة أجنبية ويستخدمونها اللغة الوسيلة لموادهم في دراساتهم الجامعية. انتهجت هذه الدراسة المنهج الوصفي لتحليل المعلومات الأولية من الاستبانة والثنائية، أما الاستبانة فهي تتوزع باللغة التاملية بين طلبة المرحلة الأولى. ونتائج هذه الدراسة أظهرت أن جزءاً كبيرا من العينة يتعلمون اللغة العربية بجانب لغتهم الأم كما أنهم يستخدمون المعاجم الإلكترونية وترجمة جوجل لفهم معاني الكلمات الغامضة في تعلمهم اللغة العربية، كما أنهم يفضلون المعاجم ثنائية اللغة وثلاثية اللغة على المعاجم أحادية اللغة من المعاجم اللغوية، ويشيرون إلى أن استخدام الترجمة الآلية وعدم المعرفة باستخدام المعاجم وعدم الرغبة في استخدامها أسباب لقلة استخدام المعاجم اللغوية.